Academic achievement in ADHD adolescents experiencing barriers to learning : perceptions of parents and learners. - Kruger, Michal (My University, 2014)
The aim of this research was to determine the perceptions of parents and learners are surrounding academic achievement and the factors which contribute to it, taking into consideration barriers to learning. The research also aimed to investigate what their perceptions are on the factors which contribute to academic achievement. There were a total of six dyads, six adolescents (middle to late adolescence) and eight parents. All of the adolescents had been diagnosed with Attention Deficit Hyperactivity Disorder (ADHD). Each of the adolescents took part in an interview and the parents took part in a separate interview. The interviews were semi-structured in nature. The findings of the study indicated that academic achievement was defined as being based on marks or on the ability of the learners to achieve their potential. The factors perceived to influence academic achievement such as peers, educators, school environment and the role of parents were found to be similar between parents and adolescents. The barrier to learning (ADHD) was not perceived as having a greater influence on academic achievement than any other factor.
Keywords: Attention-deficit hyperactivity disorder; Adolescents; Barriers to learning; Academic achievement; Parents